Synthesis of Six-Membered Cyclic Sulfonimidamides - Sen, Indira; Kloer, Daniel P.; Hall, Roger G.; Pal, Sitaram (Synthesis, 2013)
A general synthetic route to six-membered cyclic N-aryl- and N-alkyl-substituted sulfonimidamides via an intramolecular ring closure of suitably functionalised acyclic sulfonimidamides is described. The structure of this new ring system was confirmed by various analytical methods and in one example by X-ray structural analysis.
Keywords: sulfonimidamide; heterocycles; cyclisation; sulfur; intramolecular